Carcinosarcoma arising in uterine didelphys after tamoxifen therapy for breast cancer: A case report - Suprasert P. (2014)
The occurrence of uterine cancer in breast cancer patients who received tamoxifen treatment, is well described. To our knowledge, an association between uterine anomaly and uterine carcinosarcoma in these patients had not been reported. We present a case of uterine carcinosarcoma occurring in uterine didelphys of a 72-year-old breast cancer patient, who had been treated with tamoxifen for 5 years. The patient presented with large pelvic mass. The uterine anomaly was not recognized preoperatively. The patient died of disease 5 months after diagnosis. Postmenopausal women taking tamoxifen should be closely monitored for symptoms of endometrial lesions.